2012
DOI: 10.1017/s1478951512000235
|View full text |Cite
|
Sign up to set email alerts
|

“All my saints are within me”: Expressions of end-of-life spirituality

Abstract: The findings support the need for hospice/palliative care professionals to approach spirituality from other than a Judeo-Christian viewpoint, help dying persons create meaning and purpose within the context of their lives, and assist them in their desire for connectedness to faith communities and other significant individuals in their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 34 publications
2
29
0
4
Order By: Relevance
“…Patients' views on spirituality were found to be connected with family as well as related to their religious beliefs. These connections provided participants various benefits, such as meaning and purpose in life, compassion toward others and a positive spiritual influence [73][74][75]. Of the topics that assessed spirituality descriptions, 'Family' and 'God/religion' were the most commonly mentioned topic.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' views on spirituality were found to be connected with family as well as related to their religious beliefs. These connections provided participants various benefits, such as meaning and purpose in life, compassion toward others and a positive spiritual influence [73][74][75]. Of the topics that assessed spirituality descriptions, 'Family' and 'God/religion' were the most commonly mentioned topic.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of spiritual care in healthcare in assisting patients to understand the turmoil resulting from serious illness, by helping them consider the meaning and purpose of their lives, is well supported (Ming-Shium, 2006;Dobratz 2013). To neglect the spiritual needs of patients, and their families, is both ethically and legally wrong (Fiifi-Amoah, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning patients' views on spirituality, it was observed that most participants found spirituality through their religious practice and connection to a higher power, as well as through connection with friends, family and acquaintances [21,33,38]. These connections provided participants with various benefits, including meaning and purpose in life, compassion toward others and a positive spiritual influence on those who survived lifethreatening illnesses [21,33,38]. Other patients also experienced spirituality within the structure and process of work or volunteer service, through communication, mediation and activities [21,33,38].…”
Section: Review Francisca Regomentioning
confidence: 99%